The Role of Environmental Variables in Waste Stabilization Ponds' Morphodynamics - Izdori, Fides; Semiao, Andrea J. C.; Perona, Paolo (Frontiers in Environmental Science, 2019)
In management of helminth infections and transmission, the correct prediction of sludge accumulation patterns in waste stabilization ponds (WSP) is important as sedimented eggs are associated with sludge depth. However, sedimentation in WSP is complicated by the non-stationary nature of the inputs and environmental factors such as weather variables, that are mostly site specific. This paper investigates sludge accumulation patterns in the Buguruni WSP (in Dar es Salaam, Tanzania) and the role that wind and increased run-off during rainy season play. Sludge depths were measured twice; in January 2017 and January 2018. Higher sludge depths were observed close to the inlet, indicating that more helminth eggs may be recovered in the sludge around this area. A sedimentation model set in Delft3D successfully reproduced the sludge accumulation pattern near the inlet, with wind and inflow characteristics as the major driving factors. The pond inlet receives more solids and water during the rain season as a result of defective pipes and manholes, and simulations show that this has significant impacts on sludge accumulation. Improved sludge depth measurement and wind and discharge data will improve modelled sludge accumulation patterns to capture those away from the inlet. Our research has shown that neglecting maintenance of the pond, as well as the sewer system has potential severe health and environmental effects, impacting communities downstream of the WSP. This research also shows the important role that numerical modelling can play in sustainable management of WSP.